Asuhan Keperawatan Dengan Penerapan Terapi Air Rebusan Temulawak Dan Kunyit Pada Pasien Gastritis Untuk Mengurangi Nyeri Di Aplikasikan Dengan Teori Watson Di Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu Tahun 2025 - Elpina Elpina; Murwati Murwati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The percentage of the incidence of gastritis in Indonesia according to WHO is 40.8%, and the incidence of gastritis in several regions in Indonesia is quite high with a prevalence of 274,396 cases from 238,452,952 inhabitants. The purpose of this study is that researchers are able to apply temulawak and turmeric boiled water therapy to gastritis patients to reduce pain applied with Watson's theory in the Work Area of the Jembatan Kecil Health Center, Bengkulu City in 2025. The research method used in this study is a case study research with the application of temulawak and turmeric boiled water therapy to gastritis patients to reduce pain applied with Watson's theory with the number of participants in this study 2 people with the same case, namely with gastritis nursing problems. The results of the application of boiled water therapy of temulawak and turmeric are very effective in reducing pain in gastritis sufferers applied with Watson's theory in the Working Area of the Jembatan Kecil Health Center, Bengkulu City in 2025. Researchers suggest that patients and their families maintain their health, both physical, psychological and environmental, and can continue to follow the recommendations that have been given and implement and apply everything that has been taught to help patients and their families achieve optimal health.